LAS NUEVAS TECNOLOGIAS DE LA INFORMACION Y LAS COMUNICACIONES Y EL DESARROLLO HUMANO SUSTENTABLE - Bedriñana Ascarza, Aquiles (2006)
Nowadays we are living in the most important technological revolution experimented by the humanity. The New Information and Communication Technologies (NICT) are already produced by the biggest multinational companies that follow the demand which has more spending capacity. The priorities and necessities of poorest countries do not deserve attention because of limitations in the financing of research, development and innovation (R+D+I). The fact that two third - parts of humankind have not obtained from the new technologies substantial improvements in their lives and some of them go worse does not encourage. When development has to be based mainly on the capacity to process and to apply the knowledge in international networks of production and interchange, the threat of an even more unequal and divided world is not false. This work tries to explain that the so called digital gap is not problem, but the result of other more important gaps in human capital, social capital, institutional capacities, democratic governability, etc. They are make difficult the poorest countries of the world to take advantage of the immense opportunities that represent the NICT. In this work, we try to answer in some way to the following questions: 1. Can the NICT have effective impacts in reduction of the poverty? 2. Can the NICT improve the quality and equitity of education? 3. Can these impacts be noticed in the short and medium term?